Paclitaxel drug-coated balloon angioplasty for the treatment of failing arteriovenous fistulas: a single-center experience. Issue 2 (3rd March 2020) - Yazar, O.; Provoost, A.; Broughton, A.; Ghijselings, L.; Leclef, Y.; Van Calster, K.; Reginster, F.; Fourneau, I.
Abstract: Objectives: To report our experience of angioplasty with Lutonix (Bard Peripheral Vascular, Inc., Tempe, AZ) drug-coated balloon (DCB) for the treatment of failing arteriovenous fistulas (AVF). Materials and methods: Retrospective, single-center analysis consisting of 14 patients treated with Lutonix paclitaxel DCBs in the period from July 2015 through April 2017. We analyzed technical success, clinical success, primary patency of the target lesion, primary patency of the dialysis circuit, and the rate of complications. Regular follow-up of AVF patency was realized by clinical examination and duplex ultrasonography. The Kaplan–Meier survival method was applied to determine the cumulative primary patency of the target lesion and the dialysis circuit. Results: Technical success was 100% and clinical success 92.9%. There were no major or minor complications. Cumulative target lesion primary patency after DCB was 69.2% at 6 months and 31.6% at 12 months. Cumulative vascular circuit primary patency was 61.5% at 6 months and 31.6% at 12 months. Conclusion: Compared to results reported in literature with plain old balloon angioplasty (POBA), Lutonix paclitaxel DCB angioplasty proved a short-term patency benefit in treatment of dialysis AVF stenosis.